Experiences of child abuse and prolonged grief in adulthood – results from a population-based study - Rummel, Anna-Maria; Comtesse, Hannah; Rosner, Rita; Sachser, Cedric; Fegert, Jörg M.; Doering, Bettina K.; Vogel, Anna (Frontiers in Psychiatry, 2025)
BackgroundIn recent years, various risk factors for the development of prolonged grief disorder (PGD) have been discussed. While it is well established that child abuse increases the risk of various mental disorders in later life, the relationship between child abuse, including its subtypes, and PGD is barely examined.ObjectiveThe aim of this study was to assess the impact of child abuse and distinct abuse patterns on PGD symptoms in a population-based German sample.MethodsWe used self-reported data from 911 individuals (54.3 ± 17.9 years, 59.2% women) who had experienced the loss of a loved one. Participants completed demographic, loss-related and child abuse-related questions. To investigate PGD symptoms we utilized the Prolonged Grief Disorder-13+9 (PG13+9). The Childhood Trauma Questionnaire (CTQ) was employed to assess both overall child abuse severity as well as child abuse subtypes: child emotional abuse, child physical abuse, child sexual abuse. We used k-means cluster analysis to identify distinct child abuse patterns. Two hierarchical regression analyses were conducted to examine the associations between PGD symptom severity and child abuse and the identified child abuse clusters.ResultsThe prevalence rate for experiencing any child abuse was 13.5%. The occurrence of the child abuse subtypes was 7.9% for emotional abuse, 7.6% for physical abuse, and 5.9% for sexual abuse. A priori, we defined an “extreme abuse” cluster from the outliers and identified three clusters “no/low abuse”, “moderate abuse” and “high abuse” in our sample through the cluster analysis. Overall child abuse severity (ß=.13, p<0.001), “high abuse” cluster (ß=.12, p=0.001) and the a priori “extreme abuse” cluster (ß=.07, p=0.040) were significant predictors of PGD symptoms.ConclusionOur study indicates that child abuse impacts PGD symptoms. Possible hypotheses for this connection and their implications are discussed.